Voting and Popularity - Gebhard Kirchgässner (Center for Research in Economics, Management and the Arts (CREMA), 2016)
For about 45 years, vote and popularity functions have been estimated for many countries indi- cating that voting intentions as well as actual votes are influenced by economic development. The economy is, of course, not the only and probably not always the most important factor, but there is no doubt anymore that it is an important factor. The most relevant variables are still unemployment, and/or real growth, and inflation. The estimated coefficients vary considerably between countries and time periods. In papers, retrospective sociotropic voting dominates. However, the evidence is not so univocal; it rath er tells that voting has egotropic as well as sociotropic aspects, and it is prospective as well as retrospective. It is still open what roles self- interest and altruism play in voting.
Keywords: H39; 330; Vote; Popularity Function; Egotropic; Sociotropic Voting; Retrospective; Prospective Voting; Rational Voters Behavior